Soft Tissue Contraction in Body Contouring With Radiofrequency-Assisted Liposuction: A Treatment Gap Solution. (15th May 2018) - Theodorou, Spero J; Del Vecchio, Daniel; Chia, Christopher T
Abstract: Radiofrequency-assisted liposuction is a relatively new concept in energy-assisted body contouring techniques and has received instrument approval. This supplemental article reviews the clinical application of electromagnetic energy via the BodyTite (InMode Corporation, Toronto, Canada) device on soft tissues during suction lipectomy, its effect on soft tissue contraction, and its use in aesthetic body contouring in various clinical scenarios.